The zahir : a novel of obsession - Coelho, Paulo; Costa, Margaret Jull (ill., 2005)
`The Zahir', Paulo Coelho's new novel available in paperback for the first time, incorporates exclusive new content including an extra section containing interviews with Paulo and plenty of information for those for whom the book just wasn't enough